Investigating an Aggregate Mine Proposal Using the Graph Model for Conflict Resolution. Issue 6 (18th August 2022) - Philpot, Simone; Hipel, Keith W.
Abstract : Aggregates are critical resources for infrastructure and development, but mining operations can be disruptive to nearby communities. We examine a conflict arising in response to a proposed aggregate mine in the Region of Waterloo, Ontario, Canada. Drawing on participant observation, interviews, and a review of publicly available materials related to the conflict, we gain insight into the regulatory constraints and decision makers driving this conflict. We then model the ongoing conflict using the graph model for conflict resolution. A set of conflict models developed as part of in-depth sensitivity analysis are described and analyzed. Individually, the models capture possible preferences of different decision makers. A comparison of model results reflects the dominance of provincial authority in aggregate mining decisions and adds clarity to the influence of different decision makers. These models provide a basis for conducting future advanced analyses of decision-maker motivations, perceptions, and strategies.